Kepemimpinan Muhammadiyah Dan Aisyiyah Memajukan Semesta Mencerahkan Peradaban - Adityo Aprianto; Muhammad Naufal Zundan; Nadzifah Nurhasanah; Syawalludin Yusuf; Dwi Ayu Azzahra; Muhammad Raffi Goutama (Institut Nalanda, 2024)
Muhammadiyah deliberations also reflect the spirit of inclusivity and pluralism in Islam in Indonesia, where various religious views and understandings are given space to speak and contribute. In a broader context, the Muhammadiyah Conference also has an impact on social and educational development in Indonesia, because Muhammadiyah has a significant role in the sector.Through a deeper understanding of Muhammadiyah Musyawarah, we can understand how a large Islamic organization like Muhammadiyah combines Islamic values ​​with democratic principles and active participation in decision-making processes. This has inspired various groups to seek relevant solutions and innovations in dealing with social, educational and religious challenges in Indonesia.